2018
DOI: 10.1186/s12889-018-6134-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between fetal-stage exposure to the China famine and risk of diabetes mellitus in adulthood: results from the China health and retirement longitudinal study

Abstract: BackgroundThe associations of famine exposure with diabetes risk in adulthood are still unclear. This study aimed to explore the association between famine exposure in early life and risk of diabetes in adulthood.MethodsA total of 4138 subjects were selected from the data of the China Health and Retirement Longitudinal Study (CHARLS) 2011–2012. Diabetes was diagnosed as fasting plasma glucose (FPG) ≥7.0 mmol/L, glycated haemoglobin (HbA1C) > 6.5%, or self-reported diabetes. Birthdates of subjects were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Consistent with some studies [20,23,39], we did not find any larger famine effects among adults born in severely affected versus less severely affected areas. This result may be explained by a great variation of famine severity in the county-level mortality [19], which caused the misclassification of famine severity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with some studies [20,23,39], we did not find any larger famine effects among adults born in severely affected versus less severely affected areas. This result may be explained by a great variation of famine severity in the county-level mortality [19], which caused the misclassification of famine severity.…”
Section: Discussionsupporting
confidence: 92%
“…The severity of Chinese famine varied remarkably across regions and time [19]. As shown in previous studies [20][21][22][23], provincial excess mortality in 1956-62 was computed as an indicator of famine severity, and excess mortality of 50% was used to classify provinces into severely affected and less severely affected areas.…”
Section: Assessment Of Famine Exposure and Severitymentioning
confidence: 99%
“…Of these 71 articles, 24 were further excluded for various reasons (Appendix S1). Finally, 47 articles were included in the present meta‐analysis. The articles were published between 2006 and 2019, mostly published from 2014 onwards.…”
Section: Resultsmentioning
confidence: 99%
“…Foetal exposure to famine was associated with higher risks of T2DM (RR 1.37, 95% CI, 1.23‐1.52; Figure ), metabolic syndrome (RR 1.26, 95% CI, 1.07‐1.50; Figure ), hypertension (RR 1.30, 95% CI, 1.07‐1.57; Figure ), hyperglycaemia (RR 1.27, 95% CI, 1.11‐1.45; Figure ), dyslipidaemia (RR 1.48, 95% CI, 1.33‐1.66; Figure 2), obesity (RR 1.19, 95% CI, 1.02‐1.39; Figure ), overweight (RR 1.17, 95% CI, 1.07‐1.29; Figure ), coronary heart disease (RR 1.22, 95% CI, 1.00‐1.51; Figure ), and moderate‐to‐severe NAFLD (RR 1.66, 95% CI, 1.07‐2.57; Figure 3) . No association was observed for the risks of stroke (RR 1.21, 95% CI, 0.96‐1.52; Figure ) or mild NAFLD (RR 1.04, 95% CI, 0.64‐1.70; Figure 3) .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found that exposure to severe famine in the prenatal or postnatal period was associated with the development of type 2 diabetes in adulthood. Data from different periods of famine around the world have been utilized to explore the association of early life malnutrition and type 2 diabetes risk in adulthood, and the “famine effect” has been found in China and some foreign studies, including Asian, European, and African populations [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%